2008
DOI: 10.1007/s10517-008-0084-8
|View full text |Cite
|
Sign up to set email alerts
|

Naphtho[2,3-f]indole-5,10-dione aminoalkyl derivatives: A new class of topoisomerase I inhibitors

Abstract: Naphtho[2,3-f]indole-5,10-dione aminoalkyl derivatives in cytotoxic concentrations inhibit topoisomerase I, which is an important factor of antitumor activity of compounds of this chemical class. The degree of topoisomerase I inhibition with naphtho[2,3-f]indole-5,10-dione derivatives depends on the structure and position of active (aminoalkyl) groups. The mechanism of topoisomerase I inhibition with aminoalkylnaph-tho[2,3-f]indole-5,10-diones differs from specific blocking of the catalytic activity of the enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Replacement of phenolic hydroxyl groups R 1 in 63 (R ¼ dimethylamino) by 2-aminoethyleneamino moieties led to mixed results, as the potency improved for some of the cell lines and declined for others, but the sensitivity of multidrug resistant breast cancer cells to these modified candidates was completely lost [86]. Furthermore, candidate 63 (R ¼ quinuclidin-3ylamino, R 1 ¼ OH) was shown to inhibit topoisomerase I-mediated relaxation of DNA, but the suppression of the topoisomerase I activity is presumably the leading although probably not the only factor contributing to cytotoxicity of Mannich bases of naphtho [2,3-f]indole-5,10-diones [87]. Preobrazhenskaya et al have also shown that a series of single and double Mannich bases 64 (R 1 ¼ H or dialkylaminomethyl) of 3,4-bis(indol-1-yl)maleimides ( Fig.…”
Section: Anticancer and Cytotoxic Activitymentioning
confidence: 99%
“…Replacement of phenolic hydroxyl groups R 1 in 63 (R ¼ dimethylamino) by 2-aminoethyleneamino moieties led to mixed results, as the potency improved for some of the cell lines and declined for others, but the sensitivity of multidrug resistant breast cancer cells to these modified candidates was completely lost [86]. Furthermore, candidate 63 (R ¼ quinuclidin-3ylamino, R 1 ¼ OH) was shown to inhibit topoisomerase I-mediated relaxation of DNA, but the suppression of the topoisomerase I activity is presumably the leading although probably not the only factor contributing to cytotoxicity of Mannich bases of naphtho [2,3-f]indole-5,10-diones [87]. Preobrazhenskaya et al have also shown that a series of single and double Mannich bases 64 (R 1 ¼ H or dialkylaminomethyl) of 3,4-bis(indol-1-yl)maleimides ( Fig.…”
Section: Anticancer and Cytotoxic Activitymentioning
confidence: 99%